Systematic Considerations for a Ballast Water Treatment System (BWTS) Retrofits: A Review - Sari, Wanda Rulita; Gunawan, Gunawan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
As a country that has more than half of the country's total territorial waters, Indonesia is highly dependent on shipping activities. Therefore, knowledge of policy updates for each ship from IMO must also be taken into account, one of which is the policy regarding the Ballast Water Management System, which requires every ship to be installed with a Ballast Water Treatment System in order to achieve the goal of a green environment in voyage areas by inhibiting the spread of microorganisms that endanger the area that is caused by ballast water. This regulatory update then creates problems, especially for ships that have been operating for a long time, because the ship has to comply with the standards for D-1 and then also have to comply with the D-2 standards according to the time specified in the convention. So, this review article will discuss the solution to the issues with retrofitting ballast water treatment systems as the addition of a new system to the existing system on a ship that has sailed and pay attention to conceptual aspects consisting of considerations and operations to find the type of ballast water treatment that suits each ship's needs by analyzing the advantages and disadvantages of each technology type method. There is also consideration for several stages that are commonly used to determine the type of treatment, starting with assessment and planning requirements, selection of space, compliance with BWMS regulations, selection of the ballast water treatment system method, engineering drawing, installation planning, and commissioning. Apart from that, several related innovation considerations were also discussed, including the development of alternative treatment technology, which has the potential for efficiency both in operational aspects and safety standards. Based on research developments, retrofitting the Ballast Water Treatment System with the ultra-violet (UV) treatment is well known as the common treatment beside the electrolysis treatment. The results obtained show that the ultra-violet (UV) method is one of the most efficient treatments when viewed from the way it works and the time duration for the treatment process. This proves that ultra-violet treatment can produce maximum efficiency if the selection of needs and consideration of maximized aspects also exceed the safety aspect as well.